2002
DOI: 10.1159/000063533
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Pulsations in Communicating Hydrocephalus

Abstract: The traditional theory of communicating hydrocephalus has implicated the bulk flow component of CSF motion; that is, hydrocephalus is generally understood as an imbalance between CSF formation and absorption. The theory that the cause of communicating hydrocephalus is malabsorption of CSF at the arachnoid villi is not substantiated by experimental evidence or by physical reasoning. Flow-sensitive MRI has shown that nearly all CSF motion is pulsatile, and there is substantial evidence that hyperdynamic choroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 52 publications
2
117
0
5
Order By: Relevance
“…A similar hypothesis was proposed (Egnor et al, 2002) in which the cause of CH was the redistribution of CSF pulsations inside the cranium. The redistribution should be the result of the dissipation of arterial pulsation into the subarachnoid space, and the flow of the stronger arterial pulsations to the choroid plexus and capillary and venous circulation.…”
Section: Pulsatility Hypothesessupporting
confidence: 54%
See 1 more Smart Citation
“…A similar hypothesis was proposed (Egnor et al, 2002) in which the cause of CH was the redistribution of CSF pulsations inside the cranium. The redistribution should be the result of the dissipation of arterial pulsation into the subarachnoid space, and the flow of the stronger arterial pulsations to the choroid plexus and capillary and venous circulation.…”
Section: Pulsatility Hypothesessupporting
confidence: 54%
“…The explanation cannot be found in light of the classical hypothesis of CSF hydrodynamics, and therefore, in recently presented research of CH in adult rats with kaolin obstruction, Li et al (2008) concluded that the obtained experimental results do not support the theory by which mechanical obstruction of CSF absorption causes hydrocephalus. It seems that the development of CH could be a result of the redistribution of CSF pulsation in the cranium (Egnor et al, 2002;Greitz, 1993;Nagra et al, 2008) which significantly differs between the higher ventricular system pulsations and the lower subarachnoid space pulsations.…”
Section: Communicating Hydrocephalusmentioning
confidence: 99%
“…Consequently, the arterial pulse pressure transmitted to the capillary circulation would be stronger [45]. In this study, we observed that the state of intracranial hypertension induced by…”
Section: Respiratory and Pulse-driven Abnormalities In Nphmentioning
confidence: 66%
“…The transmission of arterial pulsations through the CSF is also linked to the windkessel effect [45]. This mechanism involves a progressive dampening of arterial pulsations, mostly through the CSF, in order to reach the capillary bed of the brain as a nonpulsatile flow [45,46].…”
Section: Respiratory and Pulse-driven Abnormalities In Nphmentioning
confidence: 99%
See 1 more Smart Citation